Respuesta :
Going down the first ramp:
• net force parallel to the ramp:
∑ F = W sin(60°) = m a₁
(W for weight)
• net force perpendicular to the ramp:
∑ F = N + W cos(60°) = 0
(N for normal force)
The body has mass 0.1 kg, and with g = 10 m/s², its weight is W = 1 N. So in the first equation, we get
(1 N) sin(60°) = (0.1 kg) a₁ → a₁ ≈ 8.7 m/s²
Let d₁ be the distance the body moves down the ramp, i.e. the distance along the ramp between the starting point and the point O. Then
sin(60°) = h / d₁ → d₁ = 2h/√(3) ≈ 1.15h
Given an initial speed v₁ = 3 m/s, we find the speed v₂ at point O to be
v₂² - (3 m/s)² = 2 (8.7 m/s²) d₁
v₂ ≈ √(9 m²/s² + (17.4 m/s²) (1.15h))
v₂ ≈ √(9 m²/s² + (20 m/s²) h)
Going up the second ramp:
• net parallel force:
∑ F = -Fr - W sin(30°) = m a₂
(Fr for friction)
• net perpendicular force:
∑ F = N - W cos(30°) = 0
sin(30°) = cos(60°), and cos(30°) = sin(60°), so the second equation gives N = 0.87 N. Then with µ = 0.1, we have Fr = µ N = 0.087 N. The first equation then gives
-0.087 N - 0.5 N = (0.1 kg) a₂ → a₂ ≈ -5.9 m/s²
We now have
tan(30°) = h/R → h = (2.5 m)/√3 ≈ 1.4 m
(which, by the way, tells us that v₂ ≈ 6.2 m/s)
Then the distance traveled up the ramp is
d₂ = √(h² + R ²) ≈ 2.9 m
Use this to solve for the speed at the top of the ramp:
v₃² - v₂² = 2 (-5.9 m/s²) d₂
v₃ = √((6.2 m/s)² - (11.8 m/s²) (2.9 m)) ≈ 2.0 m/s
At the top of the second ramp:
• net parallel force:
∑ F = -Fsp - W sin(30°) = m a₂
(Fsp for spring)
• net perpendicular force:
∑ F = N - W cos(30°) = 0
By Hooke's law, Fsp = kx, so in the first equation we get
-k (0.10 m) - (1 N) cos(60°) = (0.1 kg) (-5.9 m/s²)
→ k ≈ 0.87 N/m
![Ver imagen LammettHash](https://us-static.z-dn.net/files/d53/518586f82ae8a390aabdc38ec8f53a27.png)